Descripciones y notas taxonómicas sobre Antirrhea Hübner (Lepidoptera: Nymphalidae: Morphinae: Antirrheini) - Orellana, Andrés (ENTOMOTROPICA, 2007)
Antirrhea porphyrosticta phrynisca ssp. n. and Antirrhea lumejia sp. n. are described from cloud forest and lowland rainforest, respectively, in Táchira and Mérida States, western Venezuela. Antirrhea ulei Strand, 1912 is redescribed, the male and first instar larva are described for the first time, and a neotype is designated. All species treated here are illustrated.